Effect of Modern (Junk) Food in Dental Caries - Manisha Nayak (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this modern age, 21st-century people are attracted more towards the outside oily and calories rich junkfood than homemade healthy food. Especially this group includes children and youth. Either due to the tasteof tongue or due to circumstances like hostel life, they are attracted to these unhealthy fast or junk food.These junk foods are bad for physical health and especially for oral health. Under this topic, we shall discussthe influence of junk food in dental caries which is increasing day by day especially in children and youngpeople due to their modern lifestyle.